Apuntes de ilustración - Vanegas, Neftalí (Book collections on Project MUSE., 2009)
An examination of the multiple ways to address illustration and graphic design, processes and procedures of creative expression and representation. Contains the illustrations of: Neftali Vanegas, Benjamín Cárdenas, Victoria Peters, Carlos Espitia, Enrique Lara, Gióvanny Rodríguez, Mafe Mantilla and Boris Greiff.